Pengaruh Stereotip Guru Terhadap Minat Mahasiswa Bidang PAUD Menjadi Guru - Ludhfia Zahra; Ali Formen (Universitas Hamzanwadi, 2025)
This study aims to analyze the influence of teacher stereotypes on the interest of students majoring in Early Childhood Education (PAUD) in pursuing a teaching profession. Employing a quantitative research method, data were processed using IBM SPSS version 16.0. The research was conducted across three universities in Semarang: Universitas PGRI Semarang, Universitas IVET Semarang, and UIN Walisongo. The sample comprised 122 PAUD students from the 2021–2024 cohorts, selected through convenience sampling based on accessibility. Hypothesis testing was carried out using simple linear regression analysis, determination coefficient (R²), as well as F-test and t-test, to examine the relationship between teacher stereotypes (independent variable, X) and students' interest in becoming teachers (dependent variable, Y). The findings indicate that teacher stereotypes significantly influence students' interest in choosing a teaching career. A more positive stereotype correlates with a higher level of interest among students to become teachers. These results provide valuable insights for educational institutions in developing strategies to enhance the appeal of the teaching profession among students and to improve public perception of the teaching role, thereby encouraging more individuals to pursue careers in education